2020
DOI: 10.1017/s0950268820000771
|View full text |Cite
|
Sign up to set email alerts
|

Increased neutrophil percentage-to-albumin ratio is associated with all-cause mortality in patients with severe sepsis or septic shock

Abstract: There has been no study exploring the prognostic values of neutrophil percentage-to-albumin ratio (NPAR). We hypothesised that NPAR is a novel marker of inflammation and is associated with all-cause mortality in patients with severe sepsis or septic shock. Patient data were extracted from the MIMIC-III V1.4 database. Only the data for the first intensive care unit (ICU) admission of each patient were used and baseline data were extracted within 24 h after ICU admission. The clinical endpoints were 30-, 90- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 35 publications
3
61
0
Order By: Relevance
“…Our findings were consistent with the results of studies that evaluated the prognostic value of NPARs in other clinical settings including STEMI [ 16 ], acute kidney injury [ 17 ], septic shock [ 18 ], rectal cancer [ 19 ], and palliative pancreatic cancer [ 20 ]. Additionally, several studies have investigated other measurable laboratory markers related to the inflammatory response in CS.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings were consistent with the results of studies that evaluated the prognostic value of NPARs in other clinical settings including STEMI [ 16 ], acute kidney injury [ 17 ], septic shock [ 18 ], rectal cancer [ 19 ], and palliative pancreatic cancer [ 20 ]. Additionally, several studies have investigated other measurable laboratory markers related to the inflammatory response in CS.…”
Section: Discussionsupporting
confidence: 90%
“…One recent study showed that hypoalbuminemia was a frequent finding early in CS and was associated with mortality independent of other risk factors [ 15 ]. Recently, several studies have combined these two markers and found that the neutrophil percentage-to-albumin ratio (NPAR) could serve as an inflammation-based prognostic predictor in patients with STEMI [ 16 ], acute kidney injury [ 17 ], septic shock [ 18 ], rectal cancer [ 19 ], or palliative pancreatic cancer [ 20 ]. Nevertheless, to the best of our knowledge, no previous study has explored the prognostic value of NPARs in critically ill patients with CS.…”
Section: Introductionmentioning
confidence: 99%
“…As a combination of two classical clinical evaluation parameters, NPAR was proved to be an independent predictor for clinical outcomes of many diseases such as severe sepsis, acute kidney injury, and STEMI [ 9 11 ], which had the advantage of simplicity, cheapness, and timeliness. A recent study demonstrated that a higher NPAR was related to higher rates of death and reinfarction during hospitalization in patients with STEMI [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, by the calculation of NPAR, the changes of these two indicators are amplified; especially in some cases, clinicians often ignore the significance of these two indicators, for example, when the neutrophil ratio is high and the albumin is low, but both are within the normal range. Previous studies also showed that a higher NPAR was associated with clinical outcomes of many diseases such as severe sepsis and acute kidney injury [ 9 , 10 ]. In patients with ST-segment elevation myocardial infarction (STEMI), a higher NPAR was related to higher rates of death and reinfarction during hospitalization [ 11 ].…”
Section: Introductionmentioning
confidence: 98%
“…The MIMIC-III database was constructed by a collaborative research team at the Laboratory for Computational Physiology, Massachusetts Institute of Technology. To get access to the database, we complete the course "Protecting Human Research Participants" at the website of National Institutes of Health and obtained the certification (Record ID: 38292153) [17].…”
Section: Methodsmentioning
confidence: 99%